Emotion Analysis of Personalized Color of Beauty Package Based on NCD Image Positioning - Wang, Feng; Xu, Jifeng; Zhang, Hanning; Yin, Jun (Frontiers in Psychology, 2021)
Purpose Based on the Nippon Color & Design (NCD) System, this paper aims to accurately discover the color preferences and image positioning of different female groups in China, and thus to establish a color reference system which is suitable for the packaging of beauty products. Methods We first select middle-aged women in the rural area of northern China as our studied group. Then we conducted an extensive questionnaire survey on their color preferences focusing on their psychological characteristics and perception rules of emotional needs for colors. After that we extract colors from samples and classify them using the NCD color system research method. Conclusion Investigating the color preference of targeted customers to establish the image space of beauty product packaging. By applying SPSS for the factor analysis, we study the rural women in northern China whom are less concerned about fashion. We focus on the accurate positioning between the interaction of color, women and environment throughout the color design process. Our results can accurately reflect the brand definition and positioning of color semantics, and thus provide invaluable information for future beauty packaging designs and marketing promotion strategy.